2010
DOI: 10.1002/ett.1395
|View full text |Cite
|
Sign up to set email alerts
|

Transforming the distribution of OFDM signals for peak‐to‐average power ratio reduction

Abstract: SUMMARYLarge peak-to-average power ratio (PAPR) is the main drawback of orthogonal frequency division multiplexing (OFDM) systems. In this paper, a novel nonlinear scheme is proposed to reduce the PAPR. This scheme transforms the amplitude of original OFDM signals from Rayleigh distribution into beta distribution. Moreover, given different parameters, this scheme has different transformation expressions. It is demonstrated that the well-known companding schemes based on exponential function and error function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In problem (12), the functions (12a) and (12c) ensure the minimization of E |x n | 6 ; the constraint (12d) remains the average power nondecreasing; (12e) and (12f) constrain the modified signal to satisfy the EVM and spectral mask requirements, respectively; finally, (12g) keeps the pilot signals unchanged. (Note that for the optimized signal, S (X − X) = ε holds, so (12d) can be used to equivalently replace the nonconvex constraint (9).…”
Section: Convex Formulation Of CM Minimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In problem (12), the functions (12a) and (12c) ensure the minimization of E |x n | 6 ; the constraint (12d) remains the average power nondecreasing; (12e) and (12f) constrain the modified signal to satisfy the EVM and spectral mask requirements, respectively; finally, (12g) keeps the pilot signals unchanged. (Note that for the optimized signal, S (X − X) = ε holds, so (12d) can be used to equivalently replace the nonconvex constraint (9).…”
Section: Convex Formulation Of CM Minimizationmentioning
confidence: 99%
“…Now the problem (12) can be transformed to an equivalent problem with variablesX (1) and c as follows…”
Section: Convex Formulation Of CM Minimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The techniques without distortion include coding [5], selected mapping (SLM) [6] and partial transmit sequences (PTS) [7]. The techniques with distortion include repeated clipping and filtering [8] and companding [9]. Compared with the techniques without distortion, the techniques with distortion can be easily applied and the PAPR-reduction performance is very significant.…”
Section: Introductionmentioning
confidence: 97%
“…In , it is shown that under some conditions on a k and for N → ∞ , the continuous time domain OFDM signal distribution converges to the correlated complex Gaussian distribution. A different approach for modelling the discrete time domain signal is invoking the central limit theorem (CLT) . Applying the CLT to yields that the marginal distribution of x is complex normally distributed, that is, xn MathClass-rel∼scriptCscriptN ()0,σa2 for N large enough and .…”
Section: Introductionmentioning
confidence: 99%